Cost Analysis of M/M/1 and MF/MF/1 Queuing Model using ANN and Signed Distance Method - et. al., S S Mishra, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, we attempt to analyze total cost of Markovian queuing models M/M/1 and MF/MF/1by using artificial neural network that models the complex and non-linear relationship between input and output and signed distance method respectively. Total costs of the models have been subjected to variation with the change in depending parameters of arrival and service rates. An efficient algorithm has been developed in order to compute the results. Models’ respective results have been presented through tables and graphs.